Energy Materials 2017 - Liu, Xingbo; Liu, Zhengdong; Brinkman, Kyle; Das, Subodh; Dryepondt, Sebastien; Fergus, Jeffrey W.; Guo, Zhancheng; Han, Minfang; Hawk, Jeffrey A.; Horita, Teruhisa; Hosemann, Peter; Li, Jian; et al. (Springer International Publishing : Imprint: Springer, 2017)
This collection highlights materials research and innovations for a wide breadth of energy systems and technologies. The volume includes papers organized into the following sections: Energy and Environmental Issues in Materials Manufacturing and Processing Materials in Clean Power Materials for Coal-Based Power Materials for Energy Conversion with Emphasis on SOFC Materials for Gas Turbines Materials for Nuclear Energy Materials for Oil and Gas.
Keywords: Materials science.; Engineering -- Materials.; elektronické knihy; electronic books